More development - more migration? The "migration hump" and its significance for development policy co-operation with sub-Saharan Africa - Charles Martin-Shields; Benjamin Schraven; Steffen Angenendt (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Many view development co-operation as a key to reducing irregular migration from sub-Saharan Africa. However, critics note that increased socio-economic development is likely to lead to more, rather than less, migration. Historical and cross-country comparison studies have shown that emigration initially increases when economic growth and rising income levels enable countries to emerge from the status of a low-income country. Only when the status of upper middle-income country has been achieved can a decrease in international migration be anticipated. Known as a “migration hump”, this correlation between development and migration also applies for sub-Saharan Africa. However, it cannot be explained solely by rising incomes and increased education. It is also driven by other factors, including demographic transition, changes in economic structures, emulation effects in migration processes, rising inequality, credit restrictions and the lowering of migration barriers. The implication that positive socio-economic development in the countries of sub-Saharan Africa would inexorably lead to an increase in irregular migration to Europe is therefore an oversimplification. Irregular migration in particular is not driven by economic motives alone. Instead this is an example of so-called “mixed migration”, in which the drivers of voluntary and forced migration blend together. Factors such as corruption, weak rule of law, human rights infringements and fragile statehood are key drivers here. Development co-operation cannot hinder migration, due also to the fact that Africa's development is not solely dependent on it. Instead, development policy co-operation with sub-Saharan Africa should focus on promoting orderly, safe and legal migration, which in turn offers positive development potential while working to prevent forced and irregular migration. Specific development policy measures should therefore include: Migration processes influenced by development policy: The opportunities for regular migration to Germany and Europe need to be expanded and ac¬companied (for example via qualification measures). Support for intraregional migration: The efforts of the African regional organisations to control intraregional migration – which constitutes a large portion of migration movements – should be supported. Prevention of brain drain: The emigration of skilled personnel required in the countries of origin should be managed via targeted investment in training partnerships in specific sectors. Promotion of good governance, democracy and rule of law: Development policy measures in this area can make a key contribution to reducing human rights violations, and therefore decrease drivers of flight and forced displacement.
Keywords: 330; Flucht und Migration